The zebu (Bos indicus) and its crosses: development and using of Santa gertrudis to increase the production level of local breeds: Review - Bodnár, Ákos; Prágai, Andrea; Kovács, Attila (Animal welfare, Ethology and Housing Systems (AWETH), 2012)
Zebu (Bos indicus) is one of the most important domesticated species of the developing countries. There are many porposes of zebu keeping. Of course, it is an essential food source for local people, but its draught strength is also very important for land cultivation and transportation. Zebu manure (e.g. organic manuring and heating) and other byproducts (skin, blood, bone etc.) are also utilized as well. Adaptation of zebu to the special tropical and subtropical climate (mainly to arid) circumstances is excellent. This species can utilize the slight pastures with low nutrient content, and also it is able to tolerate the extreme climatic circumstances, and shows a very high resistance against tropical and subtropical deseases. Among these properties, zebu could become a dominant domesticated large ruminant of arid and semi arid areas. On the other hand, zebus are also used to improve the adaptability of some cattle breeds in the tropical- subtropical countries. Santa Gertrudis is one of the most wide-spread and used zebu (Bos indicus). and cattle (Bos taurus) crossing varieties. This breed shows a result of outstanding production performances and it can be suggested to use for improving the production indicators of local zebu breeds, such as the Malagasy zebu.